2017
DOI: 10.7567/jjap.56.06hb01
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer etching of silicon nitride using infrared annealing for short desorption time of ammonium fluorosilicate

Abstract: An atomic layer etching process for silicon nitride (Si 3 N 4 ) has been developed in which ammonium fluorosilicate [(NH 4 ) 2 SiF 6 ] is formed and desorbed using infrared annealing. The cycle of forming and removing ammonium fluorosilicate was repeated, demonstrating that the Si 3 N 4 etching depth was accurately controlled with high selectivity to SiO 2 by changing the number of cycle. An X-ray photoelectron spectroscopy peak, which had been previously assigned as N-H bond of an ammonium salt, was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…6 Thermal ALE relies on temperature and thermochemically favourable reactions to remove surface species. 10 While there have been many examples of thermal ALE of a range of materials, including: HfO 2 , 4,9,11,12 ZrO 2 , 4,12 SiO 2 , 13 , Al 2 O 3 , 12,[14][15][16][17][18] AlN, 19 AlF 3 , 20 TiO 2 , 21 TiN, 22,23 W, 24,25 WO 3 , 25 ZnO 26 and GaN 27 and for other ALE techniques including Ar neutral beam ZrO 2 , 28 plasma ALE SiO 2 , 29,30 ZnO, 31 GaN 32,33 and ALE of Si 3 N 4 34 using infrared annealing, the details of the mechanism of the ALE process still require significant work to understand. The first step in ALE is the formation of a reactive but non-volatile layer on the initial film, which is followed by a material removal step to take off only the modified layer as indicated schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…6 Thermal ALE relies on temperature and thermochemically favourable reactions to remove surface species. 10 While there have been many examples of thermal ALE of a range of materials, including: HfO 2 , 4,9,11,12 ZrO 2 , 4,12 SiO 2 , 13 , Al 2 O 3 , 12,[14][15][16][17][18] AlN, 19 AlF 3 , 20 TiO 2 , 21 TiN, 22,23 W, 24,25 WO 3 , 25 ZnO 26 and GaN 27 and for other ALE techniques including Ar neutral beam ZrO 2 , 28 plasma ALE SiO 2 , 29,30 ZnO, 31 GaN 32,33 and ALE of Si 3 N 4 34 using infrared annealing, the details of the mechanism of the ALE process still require significant work to understand. The first step in ALE is the formation of a reactive but non-volatile layer on the initial film, which is followed by a material removal step to take off only the modified layer as indicated schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] Very recently, the thermal cyclic etching of SiN has also been realized. [34][35][36] In principle, a thin surface modified layer comprising (NH 4 ) 2 SiF 6 forms on the surface in a self-limiting manner to protect a material from etching by preventing for the further exposure to etchants and can be removed by thermal annealing. 35) Additional new processing techniques have been reported that involve chemically assisted ion beam etching (CAIBE) using Cl 2 plasma for etching GaAs.…”
Section: Advances In Atomic Layer Processing For Emerging Materialsmentioning
confidence: 99%
“… 9 There are a multitude of examples for thermal ALE of various materials, including oxides (HfO 2 , 3 , 7 , 10 , 11 ZrO 2 , 3 , 11 SiO 2 , 12 WO 3 , 13 ZnO, 14 and Al 2 O 3 9 , 11 , 15 − 18 ), nitrides (including AlN, 19 GaN, 20 and TiN 21 , 22 ), fluorides (e.g., AlF 3 23 ), and some work on W. 13 , 24 26 Other ALE techniques include plasma ALE of SiO 2 , 27 , 28 ZnO, 29 and GaN, 30 , 31 and infrared annealing ALE of Si 3 N 4 . 32 Despite this effort, the atomistic details of the mechanism of thermal ALE processes are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%